Adhesion strength of ductile thin film determined by cross-sectional nanoindentation - Zhao, Dawei; Letz, Sebastian; Jank, Michael; März, Martin (International Journal of Mechanical Sciences, 2024)
Cross-sectional nanoindentation (CSN) is a powerful tool for measuring the adhesion strength of thin films. However, a quantitative assessment of interfacial properties for metal thin films on brittle substrates remains a challenge due to thin film ductility. In this work, we present a hierarchical analysis method to account for plastic dissipation during delamination. According to our observations, the CSN-induced wedge geometry is more complex than what is currently presented in literature. Therefore, we develop a three-dimensional finite element (FE) modelling strategy to simulate CSN-induced delamination. Furthermore, we present the mode mixity distribution during CSN measurement based on our simulation results. We find that a purely experimental assessment of adhesion strength by CSN for ductile thin films is imprecise due to the adhesion strength-dependent stress-state in this characterization technique. By using our combined experimental and numerical approach, the adhesion strength of EBPVD-deposited Al thin film on SiO2/Si substrate is determined as 0.577 J/m2 and an additional 20 nm thick Ti adhesion layer enhances its adhesion strength to 16.4 J/m2.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Adhesion strength characterization; Cohesive zone model; Cross-sectional nanoindentation; Ductile thin film; Finite element analysis; Mode mixity